2002
DOI: 10.1046/j.1540-8167.2002.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Loss of Connexin43 Protein in Nonischemic Dilated Cardiomyopathy with Ventricular Tachycardia

Abstract: Heterogeneous reduction of Cx43 protein may result in development of malignant ventricular arrhythmia in DCM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
59
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 7 publications
4
59
0
Order By: Relevance
“…facilitated reentry. 16,17 Furthermore, MAPK activation and Cx43 downregulation may be connected, as constitutively activated p-jnk potently reduces Cx43 levels in mouse myocardium, and p-erk has been implicated in Cx43 downregulation in liver epithelial cells. 18,19 Ongoing studies are addressing the physiological importance of the expression changes revealed in the present study, as well as expanding the analysis by means of subproteomic and transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…facilitated reentry. 16,17 Furthermore, MAPK activation and Cx43 downregulation may be connected, as constitutively activated p-jnk potently reduces Cx43 levels in mouse myocardium, and p-erk has been implicated in Cx43 downregulation in liver epithelial cells. 18,19 Ongoing studies are addressing the physiological importance of the expression changes revealed in the present study, as well as expanding the analysis by means of subproteomic and transcriptome analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneous expression of Cx43, however, has been shown to be associated with enhanced susceptibility to arrhythmias in patients, 13 dogs 14,15 and mice. 16 Spatial heterogeneity in Cx43 expression in our study was quantified (as described before) 17 and showed a significantly higher heterogeneous Cx43 expression in TAC operated compared with sham-operated mice.…”
Section: N T E R U N I V E R S I T Y C a R D I O L O G Y I N S T I mentioning
confidence: 99%
“…The gap junction channel proteins connexin43, connexin45 and connexin40 are important for cell-to-cell propagation of excitations. Downregulation of connexin43 expression is associated with an increased likelihood of ventricular tachyarrhythmias in heart failure (Kitamura et al, 2002). Other connexins, including connexin45 (Yamada et al, 2003) and connexin40 (Dupont et al, 2001), are upregulated in failing hearts, possibly as a compensation for connexin43 downregulation.…”
Section: Application Of Our Bioinformatics Analysis To Heart Failurementioning
confidence: 99%